Methods For Assessing The Development Of Students’ Professional Competence In A Digital Learning Environment (Eurasian Journal of Learning and Academic Teaching, 2026)
In the modern educational process, the rapid development of digital technologies has significantly transformed teaching and learning methods. A digital learning environment provides new opportunities for improving the quality of education and for developing students’ professional competence. The effective use of digital platforms, online assessment tools, learning management systems, and interactive educational resources allows educators to monitor and evaluate students’ knowledge, skills, and competencies more accurately and continuously. This study examines modern methods for assessing the development of students’ professional competence within a digital learning environment. Special attention is given to formative and summative assessment strategies, digital portfolios, online testing systems, project-based evaluation, and learning analytics. These approaches make it possible to track students’ progress, analyze learning outcomes, and provide timely feedback